Delivering effective counselling for people with dementia and their families: Opportunities and challenges. Issue 1 (26th May 2021) - Sass, Cara; Griffiths, Alys Wyn; Shoesmith, Emily; Charura, Divine; Nicholson, Paul
Abstract: This article explores the prospect of delivering counselling to people affected by dementia from the perspective of persons responsible for delivering an integrated dementia support service, emphasising an underpinning relational approach. Findings originate from interviews with an experienced counsellor, the counselling service co‐ordinator and people affected by dementia. Framework analysis was adopted to generate themes related to the study aims. Effective counselling delivery is reliant on the counsellor's practice philosophy and appreciation of the lived experience of dementia from a person‐centred understanding. Participants discussed the benefits to offering a holistically understanding service, supportive of the needs of people affected by dementia, and how this can affect access or uptake of counselling. Findings demonstrated that counselling is a worthwhile and effective intervention to offer to people living with dementia and family caregivers. A number of recommendations for adjusting the scope of relationship‐based counselling to promote effective delivery have been made.